Non-cell Autonomous OTX2 Homeoprotein Regulates Visual Cortex Plasticity Through Gadd45b/g. (24th April 2018) - Apulei, Jessica; Kim, Namsuk; Testa, Damien; Ribot, Jérôme; Morizet, David; Bernard, Clémence; Jourdren, Laurent; Blugeon, Corinne; Di Nardo, Ariel A; Prochiantz, Alain
Abstract: The non-cell autonomous transfer of OTX2 homeoprotein transcription factor into juvenile mouse cerebral cortex regulates parvalbumin interneuron maturation and critical period timing. By analyzing gene expression in primary visual cortex of wild-type and Otx2 +/GFP mice at plastic and nonplastic ages, we identified several putative genes implicated in Otx2-dependent visual cortex plasticity for ocular dominance. Cortical OTX2 infusion in juvenile mice induced Gadd45b/g expression through direct regulation of transcription. Intriguingly, a reverse effect was found in the adult, where reducing cortical OTX2 resulted in Gadd45b/g upregulation. Viral expression of Gadd45b in adult visual cortex directly induced ocular dominance plasticity with concomitant changes in MeCP2 foci within parvalbumin interneurons and in methylation states of several plasticity gene promoters, suggesting epigenetic regulation. This interaction provides a molecular mechanism for OTX2 to trigger critical period plasticity yet suppress adult plasticity.